Physiological Changes in Glucose Differentially Modulate the Excitability of Hypothalamic Melanin-Concentrating Hormone and Orexin Neurons In Situ - Burdakov, Denis (J Neurosci, 2005)
The physiological signaling mechanisms that link normal variations in body energy status to the activity of arousal- and metabolism-regulating brain centers are not well understood. The melanin-concentrating hormone (MCH) and orexin/hypocretin types of neurons of the lateral hypothalamus (LH) exert opposing effects on arousal and metabolism. We examined whether shifts in brain extracellular glucose that correspond to physiological changes in blood glucose can alter the electrical output of neurochemically and biophysically defined LH cells in mouse brain slices. Here, we show that physiologically relevant concentrations of glucose dose-dependently enhance the electrical excitability of MCH neurons by inducing depolarization and increasing membrane resistance. We also demonstrate that the same physiological shifts in glucose have the opposite effects on the electrical activity of orexin neurons. We propose that these direct actions of glucose on the arousal- and metabolism-regulating LH neurons play a key role in the translation of normal variations in body energy resources into appropriate changes in arousal and metabolism.